Automating EMDR-based mental health treatment in virtual reality - Mu Mu; Olive Chan; Andrew Debus; Murtada Dohan; David Nicholls; Paul Wallang; Kieran Breen (Virtual Reality, 2026)
Abstract Eye Movement Desensitisation and Reprocessing (EMDR) is a proven psychotherapy for treating trauma, yet access is severely limited due to a shortage of trained therapists and long waiting times. This paper presents the development of a VR-based EMDR application that automates therapy delivery while maintaining clinical rigour and patient engagement for trauma treatment. The system incorporates therapist-informed designs, naturalistic virtual environments, and game-inspired interaction mechanics to enhance usability and immersion. The application integrates key elements of the EMDR protocol, featuring bilateral stimulation through an interactive metronome, intuitive free-hand interactions, and calming environments designed to support different phases of the treatment. A cloud-based data management system enables remote therapist support when needed. A five-day pilot study evaluating the feasibility and usability of specific phobia treatment was conducted. Quantitative results indicated improvement in phobia response, with four out of five participants achieving subclinical phobia levels on the Improving Access to Psychological Therapies Phobia Scale (IAPT toolkit 2008). Qualitative feedback highlighted the system’s accessibility, calming design, and potential to enhance user confidence in managing phobias. These findings underscore the potential of VR-based solutions for accessible and scalable psychotherapy.